Essential basic and emergency obstetric and newborn care: From education and training to service delivery and quality of care. (23rd June 2015) - Otolorin, Emmanuel; Gomez, Patricia; Currie, Sheena; Thapa, Kusum; Dao, Blami
Abstract: Approximately 15% of expected births worldwide will result in life‐threatening complications during pregnancy, delivery, or the postpartum period. Providers skilled in emergency obstetric and newborn care (EmONC) services are essential, particularly in countries with a high burden of maternal and newborn mortality. Jhpiego and its consortia partners have implemented three global programs to build provider capacity to provide comprehensive EmONC services to women and newborns in these resource‐poor settings. Providers have been educated to deliver high‐impact maternal and newborn health interventions, such as prevention and treatment of postpartum hemorrhage and pre‐eclampsia/eclampsia and management of birth asphyxia, within the broader context of quality health services. This article describes Jhpiego's programming efforts within the framework of the basic and expanded signal functions that serve as indicators of high‐quality basic and emergency care services. Lessons learned include the importance of health facility strengthening, competency‐based provider education, global leadership, and strong government ownership and coordination as essential precursors to scale‐up of high impact evidence‐based maternal and newborn interventions in low‐resource settings.